2017
DOI: 10.21873/anticanres.12077
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-inducing Effect of Hydroquinone 5-O-Cinnamoyl Ester Analog of Renieramycin M on Non-small Cell Lung Cancer Cells

Abstract: This study revealed the potential of CIN-RM for apoptosis induction and in the development of a novel anticancer agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition, 5b increased caspase-3 protein expression (Figure 3F), an important effector protease of both the intrinsic and extrinsic pathways of apoptosis, which is generally activated by chemotherapeutic drugs (20,21). Increased apoptosis and caspase-3 expression following treatment with cinnamoyl and benzaldehyde derivatives in different types of cancer, including leukemia cells, have been reported (6,(33)(34)(35). Finally, increased Fas death receptor expression (Figure 3E) and increased Bax/Bcl-2 ratio (Table II 19).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, 5b increased caspase-3 protein expression (Figure 3F), an important effector protease of both the intrinsic and extrinsic pathways of apoptosis, which is generally activated by chemotherapeutic drugs (20,21). Increased apoptosis and caspase-3 expression following treatment with cinnamoyl and benzaldehyde derivatives in different types of cancer, including leukemia cells, have been reported (6,(33)(34)(35). Finally, increased Fas death receptor expression (Figure 3E) and increased Bax/Bcl-2 ratio (Table II 19).…”
Section: Discussionmentioning
confidence: 87%
“…Anoikis resistance is (CIN-RM), a newlysynthesized derivative of RM, has been shown to be more cytotoxic against non-small cell lung cancer cells compared to RM. CIN-RM treatment induced apoptosis by increasing apoptosis inducing factor and by activating of caspase 3 and 9 through a p53-dependent mechanism (92). Another study has reported the formation of bishydroquinone renieramycin M (HQ-RM) by modifying the quinone ring of RM.…”
Section: The Preclinical and Clinical Trials Of Cancer Therapy Using mentioning
confidence: 99%
“…In addition, anticancer activity of renieramycin T was evidenced with apoptosis-inducing effect [33]. Recently, the new series of hydroquinone monoester derivatives of renieramycin M have been reported as the potential cytotoxic agents against human lung cancer cells [34,35]. The hydroquinone analogues of renieramycin M such as hydroquinone 5-O-acetyl ester (4) and hydroquinone 5-O-cinnamoyl ester (5) significantly induced apoptosis by increasing expression of apoptosis-inducing factor [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the new series of hydroquinone monoester derivatives of renieramycin M have been reported as the potential cytotoxic agents against human lung cancer cells [34,35]. The hydroquinone analogues of renieramycin M such as hydroquinone 5-O-acetyl ester (4) and hydroquinone 5-O-cinnamoyl ester (5) significantly induced apoptosis by increasing expression of apoptosis-inducing factor [35,36]. Among various semi-synthetic derivatives, 22-O-amino ester derivative of renieramycin M, namely 22-O-(N-Boc-l-glycine) ester of renieramycin M (6), exhibits potent anticancer activity against human lung cancer, which was indicated with lower half-maximal inhibitory concentration (IC 50 ) compared to renieramycin M [34].…”
Section: Introductionmentioning
confidence: 99%